2019
DOI: 10.1158/1078-0432.ccr-18-4173
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Efficacy, and Biomarker Analysis of Pyrotinib in Combination with Capecitabine in HER2-Positive Metastatic Breast Cancer Patients: A Phase I Clinical Trial

Abstract: Purpose: This phase I study assessed the safety, tolerability, MTD, pharmacokinetics, antitumor activity, and predictive biomarkers of pyrotinib, an irreversible pan-ErbB inhibitor, in combination with capecitabine in patients with HER2positive metastatic breast cancer (MBC).Patients and Methods: Patients received oral pyrotinib 160 mg, 240 mg, 320 mg, or 400 mg once daily continually plus capecitabine 1,000 mg/m 2 twice daily on days 1 to 14 of a 21-day cycle. Pharmacokinetic blood samples were collected on d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 35 publications
4
63
0
Order By: Relevance
“…A previous study indicated that patients with EGFR mutations respond to neratinib 22 . In addition, the AE profile in this study was similar to that of previous studies 23 , 24 . Consistent with previous reports, diarrhoea was the most frequent treatment-related AE.…”
Section: Discussionsupporting
confidence: 89%
“…A previous study indicated that patients with EGFR mutations respond to neratinib 22 . In addition, the AE profile in this study was similar to that of previous studies 23 , 24 . Consistent with previous reports, diarrhoea was the most frequent treatment-related AE.…”
Section: Discussionsupporting
confidence: 89%
“…Intriguingly, the biomarker analysis of previous trials suggested that PIK3CA and TP53 mutation status in ctDNA in tumor tissues correlated with response and even PFS. 3,[18][19][20] Interestingly, our patient had the PIK3CA H1047R mutation, but the value of the detection of biomarkers in the adjuvant setting still needs to be proven. In one study, pyrotinib had a manageable toxicity profile in patients with HER2-positive metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 93%
“…Preclinical studies suggested that pyrotinib can significantly inhibit the growth of HER2 factor-driven tumor cells both in vivo and in vitro. 17 This is achieved by blocking the cell cycle in the G1 phase through inhibition of the HER2 downstream signaling pathway. In a phase II study of 15 pretreated NSCLC patients with HER2 mutations, the administration of pyrotinib 400 mg resulted in an overall response rate of 53.3% and a median PFS of 6.4 months.…”
Section: Discussionmentioning
confidence: 99%